2009
DOI: 10.1074/jbc.m808312200
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hydrophobicity at the N Terminus/Membrane Interface Impairs Gating of the Severe Combined Immunodeficiency-related ORAI1 Mutant

Abstract: Patients with severe combined immune deficiency (SCID) suffer from defective T-cell Ca 2؉ signaling. A loss of Ca 2؉ entry has been linked at the molecular level to single missense mutation R91W in the store-operated Ca 2؉ channel ORAI1. However, the mechanistic impact of this mutation on ORAI1 function remains unclear. Confocal Förster resonance energy transfer microscopy revealed that dynamic store-operated coupling of STIM1 to ORAI1 R91W was largely sustained similar to wild-type ORAI1. Characterization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 61 publications
8
75
0
Order By: Relevance
“…R91 itself is not essential, as evidenced by the normal currents carried by R91E and R91G channels (35), and therefore the defect in the R91W channel has been interpreted as interference by the bulky tryptophan side chain with channel gating or with ion flux through the pore (35)(36)(37)(38). Other substitutions of interest are R91T, which reduces the amplitude of whole-cell currents compared to wild-type ORAI1; and S89G/S90G, which increases currents (35). In the two latter cases, the inward rectifying current-voltage (I-V) curve in standard recording conditions implies that the substitutions do not alter the selectivity filter (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R91 itself is not essential, as evidenced by the normal currents carried by R91E and R91G channels (35), and therefore the defect in the R91W channel has been interpreted as interference by the bulky tryptophan side chain with channel gating or with ion flux through the pore (35)(36)(37)(38). Other substitutions of interest are R91T, which reduces the amplitude of whole-cell currents compared to wild-type ORAI1; and S89G/S90G, which increases currents (35). In the two latter cases, the inward rectifying current-voltage (I-V) curve in standard recording conditions implies that the substitutions do not alter the selectivity filter (35).…”
Section: Discussionmentioning
confidence: 99%
“…Attention has focused mainly on ORAI1 channels with the SCID mutation R91W (2) or with the experimental replacements R91V, R91L, or R91F (35), which fail to carry current upon store depletion even though the proteins are at the cell surface and interact with STIM1 (35)(36)(37)(38). R91 itself is not essential, as evidenced by the normal currents carried by R91E and R91G channels (35), and therefore the defect in the R91W channel has been interpreted as interference by the bulky tryptophan side chain with channel gating or with ion flux through the pore (35)(36)(37)(38). Other substitutions of interest are R91T, which reduces the amplitude of whole-cell currents compared to wild-type ORAI1; and S89G/S90G, which increases currents (35).…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative gating mechanism a ring of W76 side chains could be brought together during CDI to function as a hydrophobic gate, by analogy to the block of conduction by the Orai1 R91W pore mutation (Feske et al, 2006;Derler et al, 2009a). W76 could also stabilize pore conformations in which other residues form the gate, such as V102 and the adjacent hydrophobic region (McNally et al, 2012;Gudlur et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, K85E does not prevent CAD binding to the amino terminus, suggesting that this residue is required for allosteric changes leading to gate opening. R91 may serve a similar function (Derler et al 2009a). Interestingly, this membraneproximal amino-terminal region overlaps with a calmodulin (CaM) binding site (aa 68 -91), and several residues in this region (A73, Y80, W76) appear to be essential for CaM binding and Ca 2þ -dependent inactivation (Fig.…”
Section: Accumulation and Activation Of Crac Channels At Er-pm Junctionsmentioning
confidence: 99%
“…Deletion of aa 73 -84 prevents CAD binding to the amino terminus and channel opening ). Mutations such as K85E (Lis et al 2010) and R91W, the mutation found originally in T cells from SCID patients , completely prevent channel opening, apparently without preventing STIM1-Orai1 binding (Navarro-Borelly et al 2008;Derler et al 2009a), although R91W may interact with STIM1 somewhat less strongly than wild-type Orai1 (Fig. 3) (Muik et al 2011).…”
Section: Accumulation and Activation Of Crac Channels At Er-pm Junctionsmentioning
confidence: 99%